Broad-spectrum humanized monoclonal neutralizing antibody against SARS-CoV-2 variants, including the Omicron variant - Wen, Kun; Cai, Jian-Piao; Fan, Xiaodi; Zhang, Xiaojuan; Luo, Cuiting; Tang, Kai-Ming; Shuai, Huiping; Chen, Lin-Lei; Zhang, Ricky Ruiqi; Situ, Jianwen; Tsoi, Hoi-Wah; Wang, Kun; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Therapeutic monoclonal antibodies (mAbs) against the SARS-CoV-2 spike protein have been shown to improve the outcome of severe COVID-19 patients in clinical trials. However, novel variants with spike protein mutations can render many currently available mAbs ineffective. In this study, we first generated mAbs by immunizing mice with adjuvanted spike protein trimer and receptor binding domain (RBD) and generated hybridoma cells. Out of 960 clones, we identified 18 mAbs that could bind spike protein. Ten of the mAbs could attach to RBD, among which five had neutralizing activity against the ancestral strain and could block the binding between the spike protein and human ACE2. One of these mAbs, WKS13, had broad neutralizing activity against all Variants of Concern (VOCs), including the Omicron variant. Both murine or humanized version of WKS13 could reduce the lung viral load in hamsters infected with the Delta variant. Our data showed that broad-spectrum highpotency mAbs can be produced from immunized mice, which can be used in humans after humanization of the Fc region. Our method represents a versatile and rapid strategy for generating therapeutic mAbs for upcoming novel variants.